Breast cancer bone metastases: pathogenesis and therapeutic targets. (March 2018) - Brook, Naomi; Brook, Emily; Dharmarajan, Arun; Dass, Crispin R.; Chan, Arlene
Abstract: Breast cancer is the most common cancer affecting women worldwide, with bone metastases presenting as the most common site of disease recurrence. Bone metastases secondary to breast cancer negatively impacts patient survival, mobility, and quality of life. Furthermore, the clinical complications of breast cancer bone metastases are associated with significant financial burden to the individual and society. The molecular mechanisms involved in the metastasis, colonisation, and proliferation of breast cancer cells in bone are complex and involve crosstalk between breast cancer cells and the bone microenvironment. The ability of metastatic breast cancer cells to hijack normal biological processes involved in bone remodelling is a key driver of osteolytic and osteoblastic bone lesions. As such, our understanding of how breast cancer cells manipulate normal bone remodelling pathways is essential for the development of new therapeutic agents to improve patient outcomes. In this review, we discuss bone remodelling under normal physiological conditions and explore key pathways dysregulated in breast cancer metastasis to bone. We provide an overview of systemic therapies currently recommended for the treatment of breast cancer bone metastases and highlight emerging therapeutic targets.